2018
DOI: 10.1111/ijfs.13969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various salt contents on quality characteristics with or without curdlan of pork myofibrillar protein gels and the development of low‐salt pork sausages

Abstract: Summary The objective of this study was to evaluate the gelling properties of pork myofibrillar protein (MP) gels at various salt concentrations with or without curdlan, and its application to model sausages with reduced salt levels. When curdlan was incorporated into MP mixtures, cooking yield (CY) at 0.15 m salt was similar to that of 0.45 m salt (P > 0.05). Gel strength of MPs at 0.45 m salt was highest among other salt concentrations. Increased salt concentration tended to be high shear stress values, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This was in agreement with the highest gel strength and WHC (Figs and ). Lee and Chin found that, at 1.5% salt, pork myofibrillar protein gels containing curdlan showed increased hardness values, which indicated that curdlan improved the textural properties of low‐fat and low‐salt sausage. However, Hu et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was in agreement with the highest gel strength and WHC (Figs and ). Lee and Chin found that, at 1.5% salt, pork myofibrillar protein gels containing curdlan showed increased hardness values, which indicated that curdlan improved the textural properties of low‐fat and low‐salt sausage. However, Hu et al .…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bond content has a certain correlation with WHC. A small amount of hydrocolloids could bind with free water to form hydrogen bonds . However, excessive hydrocolloids prevented protein from fully unfolding and forming hydrogen bonds with water, which caused a decrease in WHC .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods have been successfully applied to reduce sodium in foods, including use of visual cues, particularly colour (Sukkwai et al ., 2018), and odour/flavour (Chokumnoyporn et al ., 2015) and use of foam‐mat salt (Chokumnoyporn et al ., 2016) as well as, the most commonly used method, that is use of salt substitutes (Cerrato‐Rodríguez et al ., 2017; Torrico & Prinyawiwatkul, 2017; Lee & Chin, 2019; Pujols et al ., 2019; Wilailux et al ., 2020; Xiong et al ., 2020). Another approach to salt reduction in foods would be the use of salt enhancer, a compound that magnifies the salty taste at a low level.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium chloride (NaCl) is used as salty condiment in human foods and affects the flavour, texture and shelf life of meat products (Ruusunen & Puolanne, ; Albarracín et al , ; Lee & Chin, ). In meat products, NaCl contributes to water and fat binding by expanding the filament lattice of myofibrils and by partially solubilising the myofibrillar proteins (Offer & Knight, ) and also contributes to colour and flavour.…”
Section: Introductionmentioning
confidence: 99%